THE CONCEPT OF SHADOW IN LATGALIAN CULTURE SPACE - Šuplinska, Ilga (Via Latgalica, 2012)
One of the prospective results of the ESF project „Linguoculturological and Socio-economic Aspects of Territorial Identity in the Development of the Region of Latgale” (2009–2012) is a linguo- territorial dictionary of Latgale, which would reveal particularity of Latgale’s historical, economic, folkloric, and literary factors in 300 cultural signs and concepts (when referring to selection of entries and the dictionary concept further see Šuplinska 2010). In the developed questionnaire „Latgola is…” (466 units) the word ‘susātivs’ (in Latgalian means ‘a shadow’)was included due to two reasons: 1) as infrequently used word in the cognition of the 21st century user of Latgalian literary language, being ousted by the word ‘āna’, which is closer to the Latvian literary language; 2) as a symbol of dualism/entirety apprehension of a personality activated in the latest literature and music (according to K. G. Jung’s archetype).When tracing formation of the concept of ‘susātivs’ the following sources have been reviewed (see the enclosed overview of sources): folkloric collections (S. Uļanovska, P. Smelters, B. Opincāne, et al.), periodical publications of the beginning and middle of the 20th century (most of the examples are found in „Drywa” newspaper (1908–1917) and its annexes) as well as the works of M. Andžāne, K. Nautris, O. Zvīdris, P. Jurciņš, J. Klīdzējs, R. Mūks; publications where the word ‘susātivs’ has been used in the title: modern poetry anthology „Susātivs” (2008) and CD „Bolts susātivs” (lyrics by A. Kūkuojs, music by Sovvaļnīks, 2010).The article is aimed at review of the concept of ‘susātivs’ (meaning ‘shadow’ in the Latvian literary language), revealing the conception of its lexical meanings, context and symbolic significance in folklore (mainly in riddles), literature, periodicals and stereotypes prevailing in the society. Semantic and symbolic ambiguity of ‘susātivs’ is demonstrated by Latgalian riddles, under the impact of Christianity’s as symbol of negation used in the early 20th century periodicals, interpretation of spiritual ‘susātivs’ appears in writings of K. Nautris, O. Zvīdrs. Shadow as the genuine (often banned or hidden) part of the personality in their texts is revealed by M. Andžāne, J. Klīdzējs, R. Mūks. White shadow as search of the self is activated in two publications: the modern poetry anthology „Susātivs” and CD „Bolts susātivs”.Some analytical psychology insights are worth to be highlighted that to e great extent have influenced the interpretation of the concept of ‘susātivs’ in this article. Firstly, according to the principle of analogy, the individual structure of psyche (consciousness, personal unconsciousness, collective consciousness; Jung 1996: 165) can be perceived as a psyche of ethnos, nation, supposedly of a country or of the world. Secondly, since the shadow includes hidden, suppressed, undesirable (even villainous) sides of personality and at the same time the normal instincts and impulses of creativity (Henderson 1997: 117), then exactly this unconscious side of psyche of Latgalian as a representative of the ethnos has affected the lack of self-esteem and has exacerbated the problems to which explanation in the reality of consciousness is not found anymore, or is not so simply detectable. Thirdly, being aware of the shadow, you can start to use it for revival of integrity and stability of the psyche, but the shadow can not be ignored, denied or suppressed for a long time. Even worse, if one opts for assimilation of it that has often happened to the Latgalian separate religious affiliation or language, or for exerting influence: when the first newspapers started, also new words were started to be mentioned frequently – Latgola and Latgalians. Why the old, real Latvians had to be started to call in other names? What to do! The Courlanders have taken the name of Latvians for them. Latvians from Inflantia were called the „Polish”people. For that reason in order not to fight the Courlanders for the word of Latvians, young journalists from Inflantia started to call themselves Latgalians (Dekters 1970: 12).When returning to the texts subject to analysis and understanding of the concept of ‘susātivs’, we should start with the analysis of this lexeme in folklore. It most frequently appears in the riddles and forms a ambiguous understanding of the lexeme: on the one hand, a sense of fatalism has been developed (You cannot escape your shadow by analogy with everybody should carry their own cross, or you cannot escape your fate), on the other hand, the notion of absolute good and absolute evil (obscure, inexplicable) as devil (also shadow). At the same time, several riddles underline that the shadow is a friend who never leaves, even more – one is walking, two will speak – is drawing attention to intuitive understanding of the creator of this riddle with regard to the fact that shadow is a part of the human psyche. Periodicals at the beginning of the 20th century underline the link of lexeme ‘susātivs’ with the human life, which is temporary, according to cognitions of Christianity, it is just a preparation for the real life, therefore exactly the negative, condemnable connotation is gradually pointed out in use of figurative meanings of lexeme ‘susātivs’.During 20’s and 30’s of the 20th century the stereotype that ‘shadow’ is something condemnable (e. g., undesirable phenomena of social or economic life are represented by a shadow: life shadows – backwardness, obscurantism, envy (Madsolas J. 1944)), or something that cannot exist separately, dependent entity (e. g., slave, servant, dog), is prevailing in periodicals, gradually also in the reader’s conscience. And this is just the time when not the most complimentary views with regard to Latvians from Latgale are developed and maintained at a national level (including today) that have established a preconceived attitude in Latvians from other regions and created the inferiority complexes in Latvians from Latgale.Initially in Latgalian himself his „shadow” was put to shame – different language (the opinion is gradually strengthened and only supported by Soviet times that this is a distorted Latvian literary language, also mixture of Slavic and Latvian language), which may not be Latvian (denial of the designation and introduction of the term Latgalian dialects), underdeveloped agriculture (cheap labour) and comparatively low level of education, certainly, also belonging to another faith and large families as a phenomenon of certain obscurantism. Gradually (most explicitly after K. Ulmanis’ coup in 1934 and unfortunately also after Latvia’s accession to the EU) the shadow was not put to shame in Latgalian himself or in individual from Latgale, but applied to the whole region (after accession to the EU also the other regions quite often are in this status of shadow).At the beginning of 20th century, with the growth in numbers of anthropology, psychology and psychoanalytical studies, also the understanding of shadow is affected by the change. In Latgalian literature it was commenced by M. Andžāne in her story „A black man, white shadow” (1947), where the main character Aleksandrs Rynčs demonstrates that it is important not to lose oneself, one’s substance. even if the society, the people do not understand it or it is not topical for the age. From this story comes the designation „white shadow”, which means the true, the deepest substance of an individual, harmony with oneself as a result of adopting and refining one’s own shadow – the inner human being.Maybe the Latgalian literature would never had seen the possibility to reduce the negative connotation of shadow, which is historically developed and strengthened in consciousness of the language user, unless there are two strong personalities, theoretically – shadow philosophers J. Klīdzējs and R. Mūks, whose works are known mainly to Latvians from other regions, in the case of R. Mūks, throughout the world. Of course their impact is indirect, at the same time in the works of the 21st century Latgalian authors there is a strong feeling of the reflection of their outlooks.Both authors emphasize the importance of respect for the shadow in development of an individual, as well as of the peoples and cultures at large. For the most part it means transformation of fear, feelings, instinctive hunches, ideas into creative energy. Exactly this meaning of shadow as question/ response about the true nature of a human being, society, is activated in two Latgalian publications: the modern poetry anthology „Susātivs” and CD „Bolts susātivs”.Strengthening of the shadow as a concept in the Latgalian literature at the beginning of the 21st century is due to the fact that, after going through a long way of transformation and getting rid of the negative connotation, Latgalians are beginning anew to recognize it as an integral part of their nature that allows them to retain their otherness – in language, tradition, attitude towards the world, which is still impressive with its naturalness and emotionality.